Promoting Second Language Learning and Intercultural Communication between Engineering and Liberal Arts Tertiary Education Students - Nik Aloesnita, Nik Mohd Alwi; Ainol Haryati, Ibrahim (IEEE, 2017)
Second (L2) or foreign (FL) language ecommunicators is essential because the non-native speakers of English are unequally distributed across the globe and the populations continue to expand greatly. Likewise, students at the tertiary level should be provided with the opportunity to develop the ability to communicate effectively in English in computermediated communication (CMC) settings. This is especially important for the students whose job may require them to collaboratively work in team across organizational and geographic boundaries around the globe. The current study explores e-communication between engineering students in Malaysia and Liberal Arts students in Japan leading to a project completion by both parties. The students work in small teams exchanging authentic evidence from both countries. Finally, they prepared a short presentation to wrap up their findings. The current study highlights the need for more similar research to understand how communication unfolds in CMC and how it can best be used to promote language learning and intercultural appreciation.